The financial performance of islamic and conventional banks before and after the adoption of financial blueprint policy in Malaysia - Dirie, Khadar Ahmed (2019)
The purpose of this research is to analyse the performance of Islamic and Conventional banks before and after the adoption of Malaysian financial blueprint policy in 2011 in terms of profitability. The study was analysed using secondary data from 2006 to 2018. Data for bank specific variables are mainly taken from the Bloomberg, DataStream and banks websites while macroeconomic indicators were mainly collected from Bank Negara Malaysia website. Ordinary Least Square (OLS) model was applied in order to identify the financial difference of Islamic and conventional banks in Malaysia. In addition, the paper also intends to identify the determinant factors that explain the variation in the banking performance models and whether there is also difference in terms of profitability between conventional and Islamic banks before and after the adoption of financial blueprint policy in Malaysia. The research question also addressed whether there is structural change in the performance’s parameters before and after the adoption of the financial blueprint policy reforms using Chow test. The results indicate that the performance of Malaysian banks was affected by asset quality, financial risk, operational efficiency, liquidity, gross domestic product, bank sector development and inflation rate across all study period. The results also compared the performance of Islamic and conventional banks before and after the adoption of the reform and it reveals that conventional banks to be more profitable than Islamic banks but the difference isn’t that big at the same time foreign banks in Malaysia seem to be performing better than local banks. . Moreover, using year 2011 as break point, the structural stability tests of banks’ performance parameters show that there is no structural change between the two periods namely before the adoption of the financial blueprint reforms and after.